Από το "Κουρείον" στο "Barbershop" Ο εκσυγχρονισμός της γραφιστικής γλώσσας στην εποχή της παγκοσμιοποίησης - Papadima, Aspasia (My University, 2019)
Following its 2004 accession to the European Union, Cyprus underwent many transformations, including in its visual language, which has been noticeably influenced by intercultural trends. In recent years, the traditional establishments called “koureion”, have been in decline, swiftly replaced by European-style hipster barber shops, thus altering the Cypriot landscape both linguistically and visually. The emerging trend across the visual landscape, which comprises color, typography and distinct graphic elements, is particularly evident on barber shop signs. The evolving visual language appears to be strikingly gender-oriented, as it is based on stereotypical structures and other features that promote contemporary representations of masculinity (Evans & Withey, 2018). Similarly, the use of English as a lingua franca on recently opened barber shop signs seems to embrace Europeanness, which reveals a “growing engagement and interdependence” between Cyprus and Europe (Modelski, 2003). Based on empirical research, using primary as well as secondary data, this paper aims to examine the shift in the local typographic landscape. With the aid of semiotic analysis on both graphic and linguistic communication, the present study investigates the ways in which the local visual language is following European cultural trends and adapting to globalization in order to keep up with the zeitgeist. Keywords: typographic landscape, barber shop signs, globalization, gender-oriented design, cultural trends, graphic design
Keywords: Tυπογραφικό τοπίο; Eπιγραφές κουρείων; Σχεδιασμός με γνώμονα το φύλο; Πολιτισμικές τάσεις; Γραφιστική